Factors Affecting Coffee Seed Farming Production (Coffea arabica L.) and Its Implications for Income - Febriyanto, Riyan; Sukmawati, Dety; Gantini, Tuti (Papanda Publisher, 2024)
ABSTRACT Coffee seed is one of the forest products with a lengthy marketing chain, in which numerous marketing agencies are involved; therefore, there is a need to improve efficiency in order to increase the value of existing coffee seed cultivation. It is regarded necessary to conduct research with the title